Distal Renal Tubular Acidosis (dRTA) Among Southeast Asian Ovalocytosis (SAO) Patients in Malaria Endemic Area of Sekotong, Lombok Island - I Gusti Ayu Nyoman Danuyanti; Tasmini -; Ahmad Hamim Sadewa (Tropical Medicine Journal, 2011)
Introduction: Southeast Asian Ovalocytosis (SAO) is caused by 27 bp deletion of the band 3 protein gene in erythrocyte membrane and characterized by oval erythrocyte. The erythroid band 3 (AE1) gene isexpressed not only in erythrocyte membranes but also in the cell membrane of α-collecting renal tubular functions in the secretion of acid in renal tubules and HCO3 -/Cl- anion exchange. An alteration of the band 3 (AE1) gene functions in cell of α-collecting renal tubules reduces HCO3-/Cl- ion exchange resulting in decreased secretion of H+ ions and disturbances in the process of pickling urine as an indicator of distal renal tubular acidosis (dRTA).Objectives: To determine the occurrence of dRTA among Southeast Asian Ovalocytosis (SAO) patients in malaria endemic area of Sekotong, Lombok Island by analyzing expression of erythroid band 3 (AE1) gene.Methods: Ovalocytosis degree determined by oval erythrocytes morphology of 20%-100% in blood film. The 27 bp deletion of band 3 (AE1) gene was analyzed by polymerase chain reaction (PCR). An indicators of the dRTA was determined the pH of urine, levels of bicarbonate (HCO3-), potassium (K+) and chloride (Cl-) in the blood.Results: The degree of ovalocytosis more than 50% was found in 35,7% individuals and below 50% was found in 64,3% individuals. Percentage of 27 bp deletion of band 3 (AE1) gene among subject of ovalocytosispatients was 35,7% (n = 28) and frequency of the dRTA among SAO patients was 20% (n = 10). Individuals with SAO do not generally have dRTA. The presence of the two conditions in the same individuals suggests that there may be a common underlying molecular defect or genetic basis for SAO and dRTA.Conclusion: There is a relationship between the 27 bp deletion protein band 3 (AE1) gene with distal renal tubular acidosis (dRTA) among Southeast Asian Ovalocytosis (SAO) patients in Sekotong, Lombok Island, even the percentage is low.Keywords: distal renal tubular acidosis, Southeast Asian Ovalocytosis, Sekotong, (Lombok Island)